2016
DOI: 10.1534/genetics.116.190967
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of the Constituent Subgenomes of the Natural Allopolyploid Rapeseed (Brassica napus L.)

Abstract: As the dynamic nature of progenitor genomes accompanies the speciation by interspecific hybridization, the extraction of the constituent subgenome(s) from a natural allopolyploid species of long history and then restitution of the progenitor(s) provides the unique opportunity to study the genome evolution and interplay. Herein, the A subgenome from the allotetraploid oilseed rape (Brassica napus L., AACC) was extracted through inducing the preferential elimination of C-subgenome chromosomes in intertribal cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…RBR manifested many significant phenotypes at multiple growth and developmental stages that differed from those of their parental B. napus lines, such as small leaf lobes, short siliques, and greater susceptibility to diseases during and after flowering in humid and high-temperature environments. Particularly, as with many other B. rapa lines, RBR showed severe self-incompatibility that resulted in poor seed set by self-pollination, although with a high pollen stainability (Zhu et al, 2016). Because its parent ZS11 is self-compatible, this result indicated that the selfincompatibility of RBR might result from the loss of C genome interaction when the A genome was extracted.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…RBR manifested many significant phenotypes at multiple growth and developmental stages that differed from those of their parental B. napus lines, such as small leaf lobes, short siliques, and greater susceptibility to diseases during and after flowering in humid and high-temperature environments. Particularly, as with many other B. rapa lines, RBR showed severe self-incompatibility that resulted in poor seed set by self-pollination, although with a high pollen stainability (Zhu et al, 2016). Because its parent ZS11 is self-compatible, this result indicated that the selfincompatibility of RBR might result from the loss of C genome interaction when the A genome was extracted.…”
Section: Introductionmentioning
confidence: 80%
“…A B. rapa line (designated as RBR, restituted B. rapa) with an "extracted" genome (A e A e ) of the allotetraploid B. napus (cultivar Zhongshuang 11; designated as ZS11) was produced previously (Zhu et al, 2016). The A and C subgenome within nucleus of B. napus was named as A n and C n , respectively.…”
Section: Plant Materials and Nomenclature Of Different Genomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing narrow genetic diversity due to selection pressure excessively focusing on quality and yield in the crop’s breeding pools has been a big challenge for breeders to enhance current levels of resistance to biotic and abiotic stresses ( Chang and de Jong, 2005 ; Gupta et al, 2016 ). Therefore, plant breeders and geneticists are greatly interested in enhancing genetic variants of crops via interspecific and somatic hybridization to transfer desirable traits from wild species ( Quiros et al, 1987 ; Du et al, 2009 ; Heneen et al, 2012 ; Chen et al, 2014 ; Kang et al, 2014 ; Zhu et al, 2016 ). As intermediate crossing products of interspecific hybridization, alien chromosome addition lines, CS lines and other aneuploidy lines not only offer the ideal opportunity to produce introgression lines, but provide a unique avenue to check heterologous gene expression and interaction between recipient genome and donor chromosome in plants ( Barthes and Ricroch, 2001 ; Zhu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%